2021
DOI: 10.1093/jee/toaa322
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Mushroom Sciarid Flies, Cultural Techniques, and Green Mold Disease Incidence on Commercial Mushroom Farms

Abstract: Many growers on mushroom farms producing white and brown varieties of Agaricus bisporus have noticed a potential association between sciarid fly (Lycoriella ingenua) pest populations and green mold (Trichoderma aggressivum) disease expression, and suspect that in addition to other preventative measures, controlling flies may be important to controlling green mold spread. In this study, we examined the association between L. ingenua populations and green mold disease incidence in commercial mushroom farms. In a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Through laboratory experiments, Mazin et al (2019) confirmed that mushroom sciarid fly, Lycoriella ingenua, acts as a vector for spreading pathogen Trichoderma aggressivum f. aggressivum, which was also supported by the experiments by (Coles et al, 2021).…”
Section: Global Production Trend Of Mushrooms and Trufflesmentioning
confidence: 62%
“…Through laboratory experiments, Mazin et al (2019) confirmed that mushroom sciarid fly, Lycoriella ingenua, acts as a vector for spreading pathogen Trichoderma aggressivum f. aggressivum, which was also supported by the experiments by (Coles et al, 2021).…”
Section: Global Production Trend Of Mushrooms and Trufflesmentioning
confidence: 62%
“…Previously accumulated insect pests and pathogens, coupled with the high temperature and humidity conditions, reduce the immunity of mushrooms, rendering them susceptible to pathogenic fungi and resulting in serious decay. The main reasons for analyzing the prevalence of rot disease were as follows: (1) the amount of pathogenic fungal inocula accumulates over time; as the first crop accumulates many pests and diseases, the second crop is prone to a large outbreak [55,56]; (2) high temperatures and humidity are conducive to disease development [46]; (3) the soil in the study regions is sticky and heavy, poorly aerated, and prone to waterlogging, favoring disease development [57]; (4) fungi in soil and compost can cause a range of diseases in P. rubrovolvatus due to soil community imbalance, and P. rubrovolvatus mycelium can act as a substrate for these fungi [58]; and (5) ants, flies, mites and snails, among other carriers, harbor Trichoderma spores, acting as vectors for pathogen transmission [59,60]. The climate in Guizhou Province is warm and humid, with abundant rainfall, and the major cultivation areas of P. rubrovolvatus mostly constitute deciduous forests.…”
Section: Discussionmentioning
confidence: 99%
“…Yields of oyster mushrooms are reduced by fly larvae feeding on developing mushroom primordia [ 16 ]. Larval and adult fungus gnats can also spread mushroom green mold disease, Trichoderma spp., by way of carrying spores on their bodies [ 17 , 18 , 19 ]. Furthermore, dead fungus gnats tend to adhere to oyster mushrooms as a contaminant increasing processing time by producers prior to shipment.…”
Section: Introductionmentioning
confidence: 99%